Penerapan Integrasi Pendidikan Karakter dalam Pembelajaran Pendidikan Islam yang Efektif di Lingkungan Sekolah - Elsa Dwiyana; Dinda Putri Azmalasari; Widya Putri Lestari; Tuti Nuriyati (Institut Agama Islam Hidayatullah Batam, 2025)
This study aims to explain how the integration of character education is implemented in Islamic Education learning in a continuous and optimal manner. The method used is a literature review with a descriptive qualitative approach by analyzing relevant scientific journals and books. The results show that the integration of character education requires synergy between teachers, the curriculum, and the school environment. Sustainable strategies such as habituation of religious values, teacher role modeling, and character evaluation are effective in shaping students' personalities holistically. However, this process faces challenges such as narrow perceptions of religious education, lack of teacher training, negative influences of social media, and limited resources. Therefore, character education in the context of Islamic Education needs to be designed systematically, collaboratively, and in accordance with current developments in order to produce intelligent, ethical, and morally upright generations.